Randomized clinical trial to evaluate two methods of caries risk assessment in schoolchildren: the CARDEC-PEL 04 study protocol - Aryane Marques Menegaz; Thays Torres do Vale Oliveira; Mariana Minatel Braga; Daniela Prócida Raggio; Maximiliano Sergio Cenci; Fausto Medeiros Mendes; Marina Sousa Azevedo (BMC, 2021)
Abstract Background Caries risk assessment is an essential element for managing and preventing dental caries in children. Individual caries risk assessment can be conducted to evaluate the presence or absence of single factors, or using multivariate models, a combination of factors. The subject has been extensively studied, but no previous research has compared whether a more elaborate and individualized method of caries risk benefits the patient than more straightforward strategies. Thus, this protocol evaluates the efficacy of two risk assessment methods for caries control in children, a simplified method based on caries experience evaluation and a multivariate method described in the literature. Methods This is a randomized, double-blind, controlled, parallel-treatment trial protocol. Two groups will be tested for two forms of caries risk assessment: an individualized and detailed multivariate method based on the guidelines of the Caries Care International 4D and another simplified process, based only on caries experience in primary and/or permanent dentition, considering the presence of decayed, missing and filled teeth using the DMFT/dmft index. Participants will be children aged 8 to 11 years, followed up at 12 and 24 months. The primary outcome will be a composite outcome representing the number of tooth surfaces requiring operative intervention (account variable). In addition, the Shapiro-Wilk normality test and Student's t-test will be performed. A multivariate analysis using negative binomial regression will compare groups in the intention-to-treat population, considering a two-tailed significance level of 5%. Discussion This is the first randomized clinical trial aiming to compare dental caries-related treatment and follow-up based on a detailed, multivariate and individualized assessment of caries risk in school-age children to a simpler risk assessment strategy based on caries experience. This study will define whether there are essential benefits to the patient that justify the choice of one method over the other. Trial registration Clinicaltrials.gov registration: NCT03969628. Registered on May 31th, 2019.